2008
DOI: 10.1038/eye.2008.17
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy combined with posterior subtenon triamcinolone acetonide injection in the treatment of choroidal neovascularization

Abstract: Purpose To evaluate the therapeutic effect of photodynamic therapy (PDT) combined with posterior subtenon injection of triamcinolone acetonide (PSTA) in the treatment of choroidal neovascularization (CNV). Methods In this retrospective case-control study, treatment outcomes at 12 months of patients with CNV were reviewed. One hundred and two consecutive patients (102 eyes) with subfoveal CNV of various causes were included. Patients in the study group (n ¼ 46) received PDT followed within 2 days by 40 mg of PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…The mean VA changes for eyes with predominantly classic CNV was +0.6 (±1.9) lines and for occult CNV was -1.75 (±3.39) lines that resulted better than controls treated with PDT alone. The incidence of IOP elevation and cataract progression was 8.7 and 6.5%, respectively, significantly lower than those reported from the studies using IVTA: 21-43% of IOP elevation, and >57% of cataract progression [55]. The pharmacokinetics of posterior sub-Tenon's triamcinolone injection is currently under investigation.…”
Section: Peri-ocular Ta In Cnvcontrasting
confidence: 52%
See 1 more Smart Citation
“…The mean VA changes for eyes with predominantly classic CNV was +0.6 (±1.9) lines and for occult CNV was -1.75 (±3.39) lines that resulted better than controls treated with PDT alone. The incidence of IOP elevation and cataract progression was 8.7 and 6.5%, respectively, significantly lower than those reported from the studies using IVTA: 21-43% of IOP elevation, and >57% of cataract progression [55]. The pharmacokinetics of posterior sub-Tenon's triamcinolone injection is currently under investigation.…”
Section: Peri-ocular Ta In Cnvcontrasting
confidence: 52%
“…The concentration level that this dose could reach in the subretinal space is still unclear, and there is no substantial agreement between the physicians, about the optimal dose to be injected in the human eye. Some authors reported good results even with lower doses of TA (2 mg-Iwama D 2008) [42] [55][56][57][58][59] with fewer side effects like cataract and glaucoma. Nevertheless, in most trials the effect of TA was transient.…”
Section: Dosagementioning
confidence: 95%
“…The poor natural history of CNV has led to several treatment options, including photodynamic therapy, thermal laser, intravitreal triamcinolone and submacular surgery; however, none of these has proven consistent in their therapeutic benefit 6–9 . More recently, treatment of subfoveal CNV in AMD has been revolutionized by anti‐vascular endothelial growth factor (anti‐VEGF) agents 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] The poor natural history of CNV has led to several treatment options, including photodynamic therapy, thermal laser, intravitreal triamcinolone and submacular surgery; however, none of these has proven consistent in their therapeutic benefit. [6][7][8][9] More recently, treatment of subfoveal CNV in AMD has been revolutionized by anti-vascular endothelial growth factor (anti-VEGF) agents. 10 Although the mechanism of VEGF upregulation in CNV is not clear, inhibition of this growth factor has been effective in closing the membrane, restoring retinal architecture and improving visual acuity (VA).…”
Section: Introductionmentioning
confidence: 99%